Macrophytes as potential biomonitors in peri-urban wetlands of the Middle Parana River (Argentina) - Alonso, Xenia (2017)
The aims of this study were to measure the concentrations of nutrients and pollutants in peri-urban wetlands, to analyze the plant morphology of the most representative macrophyte species, and to determine their potential use as biomonitors. Four wetlands in the Middle Paraná River floodplain evidencing contamination or anthropogenic impact were studied. The studied species were Typha domingensis Pers., Eichhornia crassipes (Mart.) Solms., Alternanthera philoxeroides (Mart.) Griseb., and Pistia stratiotes L. Besides, the same plant species from an uncontaminated wetland considered as control were studied. A. philoxeroides showed the highest total phosphorus (TP) concentration in leaves throughout the study, while the other species showed a higher TP concentration in roots than in leaves. Since metal concentration in A. philoxeroides tissues was always higher than in sediment, further studies focused on its phytoremediation capacity should be carried out. T. domingensis exhibited the highest Zn concentrations in roots followed by Pb, and E. crassipes presented the highest values of Pb concentrations in roots. The aerial part height of the plants from peri-urban wetlands was significantly higher than that of the plants from the control, while the root length was significantly lower. The root length of P. stratiotes showed a negative correlation with soluble reactive phosphorus (SRP) concentration in water. All the root anatomical parameters of T. domingensis and E. crassipes showed a positive correlation with nitrate and ammonium concentrations in water. The studied macrophytes evidenced a high tolerance, enabling them to grow and survive in peri-urban wetlands that receive pollution from different sources. The use of aquatic and wetland plants as contaminant bioindicators and bioaccumulators in the Middle Paraná River floodplain is completely feasible.